A new hybrid conjugate gradient algorithm as a convex combination of MMWU and RMIL nonlinear problems. Issue 3 (3rd April 2021) - Jardow, Fanar N.; Al-Naemi, Ghada M.
Abstract: In our research, a new conjugate gradient (CG) method for solving nonlinear systems of equations is introduced and studied. The proposed method defined as a convex combination between MMWU and RMIL problems to derive the new scale parameter ϑ . The sufficient descent condition has been satisfied for the suggested method, when we apply strong Wolfe line search, global convergence has been satisfied. Our numerical results show that the suggested algorithm are also more efficient.